Determinants of family planning service utilization among adolescents - Yuliati, Luluk; Wijayanti, Irfana Tri (Science Midwifery, 2023)
Efforts to improve adolescents' access to basic health services are very important for community health centers and their networks at the first level of service. So that access to adolescents in utilizing family planning services determines whether the program runs or not. The aim of this study was to identify factors influencing adolescents use of family planning services. This study is an observational study with an analytical survey method, with the cross-sectional approach. The objects in this study were all adolescents in class XI at SMK Bhakti Utama Pati, totaling 38 people. The independent variables in this study were age, knowledge about reproductive health, access to family planning services, quality of family planning services, and the dependent variable in this study was Utilisation of Family Planning Services in Adolescents. The instrument used was a questionnaire that had been tested. Univariate analysis using frequency distribution, bivariate analysis using chi-square, and multivariate analysis using multiple logistic regression. The results of the analysis with Chi-Square showed that there was a significant relationship between age (X2 = 8.306 and p=0.031), knowledge (X2 = 6.756 and p=0.009), access (X2 = 5.158 and p=0.023), and service quality (X2 = 15.454 and p = <0.001) with the utilization of family planning services in adolescents. The results showed that the independent variables in the multiple logistic regression model, namely age, knowledge, access, and service quality together were able to explain the utilization of family planning services in adolescents by 69.8% with an X2= 28.156 with p < 0.001.